Development of a novel composite sensor for evaluating lip function. (26th June 2019) - Sugano, Aki; Ofusa, Wataru; Sugito, Hiroki; Matsubayashi, Naoto; Hakkaku, Megumi; Yamada, Yoshiaki
Abstract: Objective: To test a novel sensor for assessing lip function. Methods: The electromyographic (EMG) activity of the upper orbicularis oris muscle (OOM), lip‐closing pressure (LP) and intraoral baro‐pressure (IP) were simultaneously recorded in 20 healthy subjects (10 women and 10 men) by using a novel composite sensor (CS). Subjects performed the lip‐closure, blow and suck tasks. EMG activity of the upper and lower OOMs was recorded using conventional surface electrodes to evaluate the accuracy of CS electrodes. The subjects also rated the user‐friendliness of the CS. Results: Integrated EMG signals recorded using the CS and conventional electrodes from the upper OOM were highly correlated ( r  = 0.77 ± 0.12 in women and r  = 0.81 ± 0.10 in men). The signal‐to‐noise ratio was higher with the CS than with the conventional electrodes. The mean LP during maximum lip closure, blowing and sucking ranged between 2 and 6 kPa in women and between 5 and 7 kPa in men. The corresponding IPs in women were 0.0 ± 0.5, 3.2 ± 1.4 and −4.4 ± 2.6 kPa, respectively, and in men were −0.5 ± 1.4, 4.9 ± 1.8 and −5.6 ± 2.8 kPa, respectively. All subjects rated the recording technique as excellent or good. Conclusion: The CS was highly user‐friendly and accurate in recording the EMG activity of the OOM and could simultaneously measure the LP and IP. Therefore, it could be an effective tool for evaluating lip function.